Assessment of tuberculosis knowledge among Lesotho village health workers and utilisation of their tuberculosis services by the communities they serve - Maseabata M. Ramathebane; Tiisetso J. Makatjane; Regina M. Thetsane; Motselisi Mokhethi (AOSIS, 2019)
Background: The role of village health workers (VHWs), among other roles is to educate communities about tuberculosis (TB), TB screening and its treatment. The knowledge of TB among VHWs is crucial because they will carry out their role at the community well and this will impact the overall outcome of TB treatment. Aim: The study is aimed at assessing the knowledge of TB among VHWs and households at the village level and the utilisation of VHWs' TB services. Setting: The study took place in 19 health centres from 10 districts of Lesotho. Methods: The study used a cross-sectional descriptive design. Three study populations were interviewed, two at the household level (2040 households, 8295 individuals) and one at the clinic level (723 VHW). Results: Overall, TB knowledge among VHWs for the majority of clinics except two was inadequate (below mean of 31.5). The utilisation of VHWs' TB services among community members was also low. Conclusion: Low utilisation of VHWs' TB services by community members emanated from inadequate TB knowledge of VHWs. Regular refresher training among VHWs is recommended as the way forward in order to keep VHWs abreast with new TB developments.